2019
DOI: 10.1103/physreva.99.043806
|View full text |Cite
|
Sign up to set email alerts
|

Coherent light propagation through cold atomic clouds beyond the independent scattering approximation

Abstract: We calculate the relative permittivity of a cold atomic gas under weak probe illumination, up to second order in the density. Within the framework of a diagrammatic representation method, we identify all the second order diagrams that enter into the description of the relative permittivity for coherent light transmission. These diagrams originate from pairwise position correlation and recurrent scattering. Using coupled dipole equations, we numerically simulate the coherent transmission with scalar and vector … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…In some cases, the theory can be solved even analytically, with sufficiently small atomic separations (ka) < (π/3) 1/2 needed for bistability of spatially uniform modes. The bistability threshold ka ∼ 1 applies even for the case of just two atoms and equals the separation at which the single-atom linewidth γ becomes less than the collective line shift, originating from recurrent scattering where the light is scattered more than once by the same atom [77][78][79][80][81][82].…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, the theory can be solved even analytically, with sufficiently small atomic separations (ka) < (π/3) 1/2 needed for bistability of spatially uniform modes. The bistability threshold ka ∼ 1 applies even for the case of just two atoms and equals the separation at which the single-atom linewidth γ becomes less than the collective line shift, originating from recurrent scattering where the light is scattered more than once by the same atom [77][78][79][80][81][82].…”
Section: Introductionmentioning
confidence: 99%
“…While superradiance and subradiance effects [27,28] have been reported in dilute systems (see, e.g., [29][30][31]), we found that our experimental results can be well explained, keeping superradiance and subradiance effects out of the picture. Modifications of the light scattering properties due to dipole-dipole interactions [32][33][34][35][36][37][38][39] are also not expected to play a role here.…”
Section: A Experimental Setup and Parametersmentioning
confidence: 82%
“…For high densities, the problem is difficult to solve even in the absence of external fields when * has been calculated only up to second order in ρ/k 3 0 [5,6]. Numerical methods employed in this work proved to be very useful to guide and test analytical theories in this research field [8].…”
Section: Discussionmentioning
confidence: 95%
“…In this Appendix, we present a solution of the anisotropic diffusion equation (5) with the boundary conditions (7) and (8) in a cylindrical sample depicted in the inset of Fig. 1.…”
Section: Appendix B: Solution Of the Anisotropic Diffusion Equation Fmentioning
confidence: 99%
See 1 more Smart Citation